Analisis Sistem Penyangga pada Terowongan Pengelak Proyek Bendungan Lau Simeme Kec. Sibiru-biru Kabupaten Deli Serdang, Sumatera Utara - Geovano Osvaldo Simbolon; Nurmaidah Nurmaidah (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2023)
This tunnel is an alternative structure used to divert river water during construction of the dam body. Location The tunnel is located in Kuala Deca Village, Civilville District, Deli Serdang District, North Sumatra. Since this tunnel is located under a hill, a buffer system is required within the tunnel for the tunnel to be considered safe. The purpose of this study is to analyze the entrance side stress and calculate the safety factor of the tunnel. Rock mass classification (RMR) is currently used to determine the service life of tunnels. Analysis of the upstream support system "Inlet" shows that at STA 0+ 043.000 the support system used on the upstream side of the tunnel is I conclude that it is bedrock bolts and shotcrete. A geologist gives him an RMR value between RMR 41 and 60. Mathematically, the inlet stress is 11,758 MPa and the maximum stiffness is 41.221,137 MPa/m, so the inlet safety factor is 301,14. 51,50 for roofs and walls. The Lau-Simeme Dam Tunnel is considered safe because the overall tunnel safety factor is 1,5.